Pengaruh Manajemen Kurikulum Dalam Pembelajaran Karakter Di Sekolah Dasar - Apriani, Dhea (Pedagogi: Jurnal Pendidikan Dasar, 2023)
School as an educational institution that organizes the teaching and learning process plays a very important role in the formation of good human character through education. One of the influential points in the process of forming the character of students in an educational institution is in the learning process carried out both in the classroom and outside the classroom. The purpose of this paper is to describe the implementation of curriculum management in character learning in elementary schools. The research method used in this study is a literature research method using Indonesian language journal articles for the past 5 years. Data collection techniques using descriptive qualitative techniques where researchers take data by drawing conclusions. The results of the literature review show that the influence of curriculum management can increase character strengthening in elementary schools.